2014
DOI: 10.1136/amiajnl-2014-003144
|View full text |Cite
|
Sign up to set email alerts
|

VA OpenNotes: exploring the experiences of early patient adopters with access to clinical notes

Abstract: Initial assessment of the patient experience within the first 9 months of availability provides evidence that patients both value and benefit from online access to clinical notes. These findings are congruent with OpenNotes study findings on a broader scale. Additional outreach and education is needed to enhance patient awareness. Healthcare professionals should author notes keeping in mind the opportunity patient access presents for enhanced communication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
94
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(104 citation statements)
references
References 36 publications
10
94
0
Order By: Relevance
“…Earnest et al 70 reported that of all medical record components offered online, patients with congestive heart failure accessed their visit notes the most and felt empowered by this option. Patients in studies by Bjoernes et al 41 and Pagliari et al 31 were positive about experiences with open medical records, reporting improved communication and trust between patients and professionals, confidence in self-care, compliance and accuracy of records (also see Pyper et al ,71 Honeyman et al ,72 Woods et al ,49 Nazi et al 50). In addition, Pyper et al attributed transparent clinician–patient interaction through personal health records to enhanced patient responsibility, participation and knowledge, overall health and quality of life, improved accessibility and relationships with health professionals, better care collaboration, and decreased errors and costs.…”
Section: Discussionmentioning
confidence: 99%
“…Earnest et al 70 reported that of all medical record components offered online, patients with congestive heart failure accessed their visit notes the most and felt empowered by this option. Patients in studies by Bjoernes et al 41 and Pagliari et al 31 were positive about experiences with open medical records, reporting improved communication and trust between patients and professionals, confidence in self-care, compliance and accuracy of records (also see Pyper et al ,71 Honeyman et al ,72 Woods et al ,49 Nazi et al 50). In addition, Pyper et al attributed transparent clinician–patient interaction through personal health records to enhanced patient responsibility, participation and knowledge, overall health and quality of life, improved accessibility and relationships with health professionals, better care collaboration, and decreased errors and costs.…”
Section: Discussionmentioning
confidence: 99%
“…1 Sharing notes with patients may yield important health benefits, including increased patient empowerment and improved medication adherence. 2,3 Seeing written information, including notes, helps patients remember the plan of care, reinforces patients' positive behaviors and strengthens the patient-doctor alliance. 2,[4][5][6] As fully transparent medical records proliferate, many questions remain unanswered (Table 1).…”
Section: Introductionmentioning
confidence: 98%
“…Considering that around 70 per cent of Veterans access health care through non-VA facilities, tools such as "Blue Button" could help improve the quality and coordination of care (Hynes et al, 2007;Nazi et al, 2014). Barriers to improved access are the same as those of access to MyHealtheVet (see Subsection 3.5.5.2).…”
Section: Data Exchange With Veterans Directlymentioning
confidence: 99%
“…After a successful pilot in which researchers found that "Viewing their records appears to empower patients and enhance their contributions to care" (Woods et al, 2013), VA in 2013 made clinical notes available through MyHealtheVet, including outpatient primary care and specialty visit notes, discharge summaries, and emergency department visit notes (VA, 2013a). A survey of early adopters found that a majority of the users of VA's version, called VA Notes, agreed that "accessing their notes will help them to do a better job of taking medications as prescribed (80.1 per cent) and be better prepared for clinic visits (88.6 per cent)" (Nazi et al, 2014).…”
Section: Myhealthevetmentioning
confidence: 99%